Effects of Customer Loyalty Determinants in Social Media Context on Social Customer Loyalty - Alenazi, Sultan Alaswad; Alanazi, Tawfeeq M. (The journal of contemporary issues in business and government, 2021)
The aim of this study is to identify determinants of customer loyalty based on literature review and to examine the effects of these determinants on social customer loyalty. Using a questionnaire developed based on previous studies, 352 complete and valid responses collected form 500 users of social media of banks in Saudi Arabia. Four hypotheses were suggested, including four independent variables (brand equity, customer satisfaction, customer trust, customer engagement and co-production) conceptualized in terms of social media and one dependent variable (social customer loyalty). In agreement with many previous studies, all hypotheses were supported except the hypothesis that co-production via social media (social co-production) significantly affects customer loyalty experienced through social media (social customer satisfaction). In accordance with these results, banks are required to consider social media applications not only for the purpose of brand promotion and awareness, but also to constitute customer loyalty by paying more attention to determinants of customer loyalty such as those identified in this study.